Creating Intersectional Subjects: A Critical Discourse Analysis of Health Science Breastfeeding Research. Issue 1 (January 2022) - Carter, Shannon K.; Stone, Ashley; Graham, Lain; Cox, Jonathan M.
Reducing race disparities in breastfeeding has become a health objective in the United States, spurring research aimed to identify causes and consequences of disparate rates. This study uses critical discourse analysis to assess how Black women are constructed in 80 quantitative health science research articles on breastfeeding disparities in the United States. Our analysis is grounded in critical race and intersectionality scholarship, which argues that researchers often incorrectly treat race and its intersections as causal mechanisms. Our findings reveal two distinct representations. Most commonly, race, gender, and their intersection are portrayed as essential characteristics of individuals. Black women are portrayed as a fixed category, possessing characteristics that inhibit breastfeeding; policy implications focus on modifying Black women's characteristics to increase breastfeeding. Less commonly, Black women are portrayed as a diverse group who occupy a social position in society resulting from similar social and material conditions, seeking to identify factors that facilitate or inhibit breastfeeding. Policy implications emphasize mitigating structural barriers that disproportionately impact some Black women. We contribute to existing knowledge by demonstrating how dominant health science approaches provide evidence for health promotion campaigns that are unlikely to reduce health disparities and may do more harm than good to Black women. We also demonstrate the existence of a problematic knowledge set about Black women's reproductive and infant feeding practices that is both ahistorical and decontextualized.